Effect of illuminance and spectrum on peripheral obstacle detection by pedestrians. (April 2017) - Uttley, J; Fotios, S; Cheal, C
Obstacle detection is an important visual task for pedestrians. An experiment was carried out to measure the ability to detect peripheral obstacles under variations of illuminance and scotopic/photopic luminance ratio and with older and younger test participants. The LED array used in this work enabled scotopic/photopic ratio to be varied whilst chromaticity was held constant. The tests employed a full-scale model with dynamic fixation and walking to better simulate pedestrian experience than in past work. Detection performance increased with illuminance, reaching a plateau at 2.0 lux. A higher scotopic/photopic ratio improved obstacle detection but only at the lowest illuminance used in this study (0.2 lux). Older participants showed poorer obstacle detection performance than younger participants but again only at the lowest illuminance.